2016
DOI: 10.1021/acs.jpcb.6b04066
|View full text |Cite
|
Sign up to set email alerts
|

Local Structure in Terms of Nearest-Neighbor Approach in 1-Butyl-3-methylimidazolium-Based Ionic Liquids: MD Simulations

Abstract: This document is the Accepted Manuscript version of a Published Work that appeared in final form in the Journal of Physical Chemistry B, copyright © American Chemical Society after peer review and technical editing by the publisher. To access the final edited and published work see http://pubs.acs.org/doi/abs/10.1021/acs.jpcb.6b04066.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 92 publications
2
37
1
Order By: Relevance
“…First, the larger isotope effects measured on the 19 F resonances of BF 4 − versus PF 6 − isotopologues correlate with the greater electron density on the F atoms in the former anion . In addition, the fact that the variations in Δ 19 F(H,D) values follow different trends in [C 4 mim]PF 6 and [C 4 mim]BF 4 isotopologues is likely related to differences in interaction geometries of these anions with the imidazolium cation . This suggests that isotope effect data could not only be employed to study H‐bond relative strength in N , N ′‐dialkylimidazolium salts, but also to scrutinize their local structure and ion ordering.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…First, the larger isotope effects measured on the 19 F resonances of BF 4 − versus PF 6 − isotopologues correlate with the greater electron density on the F atoms in the former anion . In addition, the fact that the variations in Δ 19 F(H,D) values follow different trends in [C 4 mim]PF 6 and [C 4 mim]BF 4 isotopologues is likely related to differences in interaction geometries of these anions with the imidazolium cation . This suggests that isotope effect data could not only be employed to study H‐bond relative strength in N , N ′‐dialkylimidazolium salts, but also to scrutinize their local structure and ion ordering.…”
Section: Resultsmentioning
confidence: 99%
“…One involves the anion as the H‐bond acceptor and the C―H groups on the imidazolium ring as the H‐bond donors and is often referred to as aromatic or primary H‐bonds, while the other, known as aliphatic or secondary H‐bonds, is formed between the anion and C―H groups on the N ‐alkyl sidechains. While weaker, quantum theory of atoms in molecules (QTAIM) calculations have shown that the strengths of aliphatic C―H⋅⋅⋅X H‐bonds are in some cases comparable to those of their aromatic counterparts, suggesting that these interactions also play a central role in the ordering of the local structure of ILs . To date, however, there is virtually no experimental data that can corroborate these theoretical results.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations